2018
DOI: 10.5430/wje.v8n5p112
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Argumentative Text Pattern Teaching on Success of Constituting Argumentative Text Elements

Abstract: The aim of this study is to view how argumentative text pattern teaching influences constituting argumentative essayelements. The study was performed according to one-group pre-test post-test design. The study was carried out inspring term of 2017-2018 academic year and it lasted for five weeks. 33 prospective teachers who took the course ofText Producing Techniques participated in the study. The data of study were collected through 132 argumentativeessays which prospective teachers wrote and Argumentative Tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Argumentative texts have traditionally been seen as a tool for functional training in identifying diverse perspectives and their respective bases of support (Colombo, 2018). This textual typology, in fact, perfectly sums up the argumentative procedure -one argues a thesis about an argument and tries to provide supporting arguments or answer various objections to convince others of the goodness of the thesis (Lo Feudo, 2018;Özdemir, 2018). Training oneself to recognize and identify the six key elements -problem, thesis, reasons, antithesis, evidence, and conclusion -allows one to reconstruct the underlying thread of the argumentative proceeding (Özdemir, 2018).…”
Section: Background Argumentative Skills In Post-digitalitymentioning
confidence: 99%
“…Argumentative texts have traditionally been seen as a tool for functional training in identifying diverse perspectives and their respective bases of support (Colombo, 2018). This textual typology, in fact, perfectly sums up the argumentative procedure -one argues a thesis about an argument and tries to provide supporting arguments or answer various objections to convince others of the goodness of the thesis (Lo Feudo, 2018;Özdemir, 2018). Training oneself to recognize and identify the six key elements -problem, thesis, reasons, antithesis, evidence, and conclusion -allows one to reconstruct the underlying thread of the argumentative proceeding (Özdemir, 2018).…”
Section: Background Argumentative Skills In Post-digitalitymentioning
confidence: 99%
“…Since then, a standard Toulmin model of argument has been viewed as the inclusion of six elements: claim (an arguable assertion), data (the evidence to support and justify the claim), warrant (the reasoning that connects data and claim), backing (the assumptions that reinforce the warrant), qualifier (the strength conferred by the warrant), and rebuttal (the conditions in which the claim does not hold true). The overall quality of argumentative writing is more related to the quality of argument than the mere presence of the argument elements ( Paek and Kang, 2017 ; Özdemir, 2018 ; Hamam, 2020 ; Osman and Januin, 2021 ). Specifically, a good argumentative writing is not the one that only focuses on “the surface structure, or the shell of the argument” ( Stapleton and Wu, 2015 , p. 12) or that overemphasizes on structural elements of argument at the expense of quality of logic and evidence ( Macagno and Konstantinidou, 2013 ; Abdollahzadeh et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that students commonly provided the claim in their essay. Half of them did not provide such data, and counterclaim, they also did not provide evidence for counterclaims and omitted the conclusion in their writing [16]. The argumentative papers of L2 University students included two fundamental elements of argument they are claim and ground [11].…”
Section: Introductionmentioning
confidence: 99%